SOSIALISASI SEX EDUCATION PADA ANAK DI SDN 1 MOJOWARNO JOMBANG - Peni Haryanti; Diastuti, Indah Mei; Hidayati, Athi’; Aziz , Abd. (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2022)
The high number of cases of violence against children in Indonesia, especially in Jombang Regency, has become the main topic in the community and has even become a national news headline. Sexual violence against children is often carried out by those closest to them, so it is difficult for children to fight back. Even children are afraid to report this, one of the reasons is the lack of acceptable sex received by children. The role of the closest people, especially parents and teachers, is needed to teach sex education so that it is not a taboo topic in society. So that if a case occurs, it will be detected earlier and handled faster. The implementation of community service activities carried out by lecturers and students of the University of Hasyim Asy'ari Tebuireng Jombang with the title "Socialization of Sex education for Children at SDN 1 Mojowarno Jombang" was held on Monday, August 22, 2022 which took place at SDN 1 Mojowarno, Jombang Regency. Socialization activities are carried out through lectures, questions and answers, and discussions as well as singing songs according to the socialization theme. The result of this socialization activity is that it is easy for children to understand the material, this is evidenced by the results of the questionnaire given, which is 85% of children really understand the material given. In addition, 100% of the participating children attended and hoped that the participants would have similar or sustainable activities. Conclusion partners have an understanding of the importance of sex education from an early age. There are many benefits to understanding sex education apart from preventing sexual violence against children, but also preventing children from sexual activities that are harmful to children